PENGARUH MOTIVASI DAN GENDER TERHADAP MINAT LULUSAN AKUNTANSI MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI (PPAK):STUDIKASUS PADALULUSAN PROGRAM STUDIAKUNTANSI UPI BANDUNG - Ananda Aprizal, - (2012)
The purpose of this study was to determine the effect of gender on motivation and interest in accounting graduates followed the Accounting Profession (PPAk). The research method used in this research is descriptive research method with a case study approach. The sampling technique used random sampling techniques. Thus the sample in this study are the alumni of UPI accounting courses. Data analysis technique used is to use a questionnaire to be tested quality with test validity and test reliability. Distributed questionnaires containing 35 questions that must be filled out by respondents. To test this hypothesis, analysis used the F Test and Test T. The results showed that the motivational qualities, careers, and economic interests to follow a positive influence on Educational Professional Accounting (PPAk) with a significance value probifitabilitas value of 0.000, 0.007, 031 or smaller than α (0.05). While gender has significance probifitabilitas value of 0.046 or smaller α (0.05), in other words, gender has a positive effect on interest following the Accounting Profession (PPAk). While the motivation and gender affects follow simultaneously to the interests of Education Professional Accounting (PPAk) of 70.03% through the coefficient of determination (kd). Keywords: Motivation, Gender, Interest.